Increased active pulmonary tuberculosis risk from sharing bong of cannabis: a case–control study from Thailand - Chumchuen, Kemmapon; Chongsuvivatwong, Virasakdi (Frontiers in Public Health, 2024)
IntroductionTuberculosis (TB) is a chronic lung disease caused by Mycobacterium tuberculosis. Tobacco smoking and sharing of instruments have been reported to increase TB risk. In 2022, cannabis was legalized in Thailand. To address for the potential increase in cannabis use after legalization and the reported increased TB risk associated with cannabis usage, we aimed to estimate the odds ratio and population-attributable fraction (PAF) of different types of cannabis use.Materials and methodsA matched case–control study was conducted in the Songkhla Province of Southern Thailand in 2023. Face-to-face interviews were conducted to collect information on cannabis consumption. Multivariate logistic regression was performed to estimate the odds ratios representing TB risk from the independent variables. PAF was also calculated to compare the public health impacts of the variables.ResultsAmong the 148 TB cases and 117 healthy controls, we observed lower socioeconomic status and higher proportions of tobacco and alcohol use in these cases. Eleven percent of the controls were current cannabis users, while nearly 19% had ever experienced cannabis use. The proportions of ever-used, smoked, and shared cannabis use were significantly higher in these cases. After adjusting for covariates, the best-fit model showed an odds ratio of 4.22 (95% confidence interval: 1.47–12.07) for smoking and sharing a bong of cannabis. No statistical significance was found for the other types of consumption. PAF of smoked and shared bongs of cannabis was 12.16, which was slightly lower than that found in smoking tobacco (12.62).ConclusionIncreased numbers of cannabis users, especially shared smokers, may have an impact on TB risk in lower-middle-income countries, where TB is already highly prevalent.